Gestación - Ramírez, Esteban (Filmmaker); Silva, María; Silva, María; Álvarez, Adriana; Román, Edgar (Cinetel, 2009)
"Gestation is the story of Jessie, a girl living with her single mother in San José, Costa Rica. A gifted young woman with a modest upbringing, Jessie attends a private Catholic school on a scholarship. There she meets Teo, another only-child brought up by his strict, wealthy mother. The two fall in love but are soon faced with an unwanted pregnancy, a responsibility that neither is ready for. Class distinctions and social pressure come to a head in this impressive, thoughtful drama of young love. Based on a true story."--Canadian Film Institute.